2016
DOI: 10.1186/s40463-016-0141-7
|View full text |Cite
|
Sign up to set email alerts
|

The McGill Thyroid Nodule Score’s (MTNS+) role in the investigation of thyroid nodules with benign ultrasound guided fine needle aspiration biopsies: a retrospective review

Abstract: BackgroundUltrasound guided fine needle aspiration (USFNA) biopsies of thyroid nodules sometimes create a decision-making dilemma for surgeons as they may yield falsely benign results. The McGill Thyroid Nodule Score + (MTNS+) was developed to aid in clinical guidance regarding the management of patients with these USFNA results. The aim of this study was to assess the MTNS+ as a clinical tool in patients with benign preoperative thyroid nodule USFNAs and to analyze the relationship between nodule size and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(33 reference statements)
0
6
0
1
Order By: Relevance
“…A retrospective study including 3297 patients with proven PTC found the highest odds ratio for malignancy (41-53) in patients with malignant and suspicious for malignancy FNA results, compared with 9 for high risk ultrasound features and 13 for the BRAF mutation. A nomogram that incorporates these variables into a more precise cancer estimate was proposed; similar models are available 113182183184185186187188. A study using the K-TIRADS classification and the FNA cytology result confirmed the expected relation between pre-test probability of malignancy based on ultrasound and FNA result.…”
Section: Estimating the Risk Of Thyroid Cancer And Management After Tmentioning
confidence: 90%
“…A retrospective study including 3297 patients with proven PTC found the highest odds ratio for malignancy (41-53) in patients with malignant and suspicious for malignancy FNA results, compared with 9 for high risk ultrasound features and 13 for the BRAF mutation. A nomogram that incorporates these variables into a more precise cancer estimate was proposed; similar models are available 113182183184185186187188. A study using the K-TIRADS classification and the FNA cytology result confirmed the expected relation between pre-test probability of malignancy based on ultrasound and FNA result.…”
Section: Estimating the Risk Of Thyroid Cancer And Management After Tmentioning
confidence: 90%
“…However, it is clear that thyroid nodule size on ultrasound is a poor predictor of malignancy when used alone for the assessment and management of thyroid nodules [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Bizim çalışmamızda opere edilen dev nodüllerde malignite oranı %14,40 bulunmuştur. Çalışmaların büyük bir kısmında dev nodüllerde malignite oranı daha küçük çaptaki nodüllere benzer bulunurken, [12][13][14] bir kısmında daha düşük 15,16 bir kısmında ise daha fazla olarak raporlanmıştır. 17,18 Yakın zamanda yapılmış 14 çalışmanın ele alındığı bir meta analizde <4 cm 16778 hastada malignite oranı ≥ 4 cm 4660 hasta ile karşılaştırıldığında anlamlı farklılık saptanmamıştır (%19'a karşılık 20,9 p =0,87 %5 CI 0,62-1,22 Bizim çalışmamızda ultrasonografik özellikler benign ve malignnodüllerde benzer çıkmıştır.…”
Section: Discussionunclassified